2007
DOI: 10.1029/2006jd007592
|View full text |Cite
|
Sign up to set email alerts
|

In situ measurements of trace gases and aerosol optical properties at a rural site in northern China during East Asian Study of Tropospheric Aerosols: An International Regional Experiment 2005

Abstract: [1] In situ measurements of trace gases and aerosol optical properties were made in March 2005 at Xianghe (39.798°N, 116.958°E, 35 m), a rural site about 70 km southeast, and generally downwind of the Beijing metropolitan area. High pollutant levels were observed during the experiment, with CO (1.09 ± 1.02 ppmv, average ± standard deviation), SO 2 (17.8 ± 15.7 ppbv), NO y (26.0 ± 24.0 ppbv), aerosol scattering coefficients (b sp , (468 ± 472) Â 10 À6 m À1 ), and aerosol absorption coefficients (b ap , (65 ± 75… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
123
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(139 citation statements)
references
References 65 publications
13
123
3
Order By: Relevance
“…Energy structure optimization, for example, reducing coal consumption in Beijing, will improve the poor air condition and change the slope and intercept of the linear regression. The pollutants CO, SO 2 and NO 2 are excellent indicators of different CO 2 sources (Lopez et al, 2013;Newman et al, 2013;Djuricin et al, 2010;Li et al, 2007), and data on these pollutants combined with the atmospheric CO 2 mixing ratio and δ 13 C measurements will improve our understanding of carbon cycle processes in urban ecosystems.…”
Section: The Relationship Between Atmospheric Co 2 Isotope Compositiomentioning
confidence: 99%
“…Energy structure optimization, for example, reducing coal consumption in Beijing, will improve the poor air condition and change the slope and intercept of the linear regression. The pollutants CO, SO 2 and NO 2 are excellent indicators of different CO 2 sources (Lopez et al, 2013;Newman et al, 2013;Djuricin et al, 2010;Li et al, 2007), and data on these pollutants combined with the atmospheric CO 2 mixing ratio and δ 13 C measurements will improve our understanding of carbon cycle processes in urban ecosystems.…”
Section: The Relationship Between Atmospheric Co 2 Isotope Compositiomentioning
confidence: 99%
“…For example, the frequency for the occurrence of new particle formation events is 50%, 20%, 35%, and 45% in the spring, summer, fall, and winter, respectively (11). In addition, a springtime periodic cycle of aerosol optical thickness and trace gaseous species (i.e., sulfur dioxide, carbon monoxide, nitrogen oxides, and ozone) has been previously identified at a rural site in northern China (28).…”
Section: Significancementioning
confidence: 99%
“…However, these two nearly continuous dust events (2 and 3 May; intervals of only a few hours) originated from different emission sources according to the 60-h HYSPLIT air-mass back trajectories (Kalkstein et al, 1987;Stunder, 1997;Draxier and Hess, 1998;Draxler and Rolph, 2008;Huang et al, 2008a;Zhang et al, 2013). These air-mass back trajectories have been considered by previous studies to be an effective method of tracking the transport of dust events (Zhang et al, 2003a, b;Huang et al, 2010;Chen et al, 2013) and have been 29-May-08 5:00-23:00 910 ± 265 92 ± 39 27.0 ± 6.0 0.76 ± 0.04 applied in deserts such as the Taklimakan (Li et al, 2007;Huang et al, 2008a;Zhou et al, 2013) and Mongolia Gobi (Xu 2004;Zhang et al, 2013 to minimum values of 11.3 and 50 Mm -1 with maximum/ minimum ratios of around 2 and 3, respectively, during the morning of 10 April 2008, but the decreasing trends were smaller than that of the PM 10 variation. While the dust event occurred, the increased SSA was consistent with the similar changes in PM 10 .…”
Section: Comparison Of Aerosol Properties Of Dust Events and Air Pollmentioning
confidence: 99%
“…The daily maximum PM 10 could exceed 2519 µg m -3 during dust events in spring. Previous studies have indicated that fossil fuel and biomass burning occur more dominantly from November to February (hereafter referred to as the cold season) over northern China, resulting in serious local air pollution (Wang et al, 2004;Sun et al, 2005;Li et al, 2007;Yuan et al, 2008 , respectively. Although the concentration of PM 10 was highest in March- were not only determined by PM 10 but also depended on the particle size distribution and the compositions of chemical species (Hegg et al, 2009(Hegg et al, , 2010.…”
Section: Temporal Variability Of Aerosol Propertiesmentioning
confidence: 99%
See 1 more Smart Citation